Job Satisfaction in Remote Work: The Role of Positive Spillover from Work to Family and Work–Life Balance - García-Salirrosas, Elizabeth Emperatriz (2023)
The objective of this research is to propose and validate a theoretical model that explains job satisfaction in remote work influenced by family-supportive supervisory behaviors (FSSBs) and, in addition, to evaluate the mediating role of work-to-family positive spillover (WFPS) and work–life balance (WLB) in this influence. A non-experimental cross-sectional study was conducted using a self-administered survey to a sample of 396 teleworkers in Lima, Peru. The hypothesized model was analyzed using PLS-SEM based structural equation modeling. The results show that FSSB has a direct effect on both job satisfaction in remote work and WFPS and WLB. In addition, it shows that WFPS and WLB have positive effects on job satisfaction in remote work. Also, the results show that WFPS and WLB have a mediating role in the influence of FSSB on job satisfaction in remote work. In conclusion, this study highlights the importance of supervisor behavior, positive work-to-family spillover, and work–life balance in remote workers’ job satisfaction. It is suggested that companies adopt policies and practices that encourage work–life balance as well as a favorable supervisory environment.